2017
DOI: 10.1183/13993003.01959-2016
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 100% oxygen on tidal breathing parameters in preschool children

Abstract: The multiple-breath nitrogen washout (MBN 2 W) test assesses ventilation distribution by determining the number of functional residual capacity (FRC) lung turnovers required for tidal breathing of 100% oxygen to wash out resident nitrogen from the lungs [1]. In particular, the test has gained significant interest as a tool for monitoring disease progression and prognosis in children with lung disease, with a specific focus on cystic fibrosis (CF) due to its ability to discriminate between health and disease [2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Taking all into account, it seems unlikely that the different software versions used in our study with their inherent algorithms to process signals to MBW parameters are a major determinant contributing to differences between N 2 -and SF 6 -LCI observed. Some studies detected a decrease in VT during inhalation of 100% O 2 in infants, preschool children, and even young adults of up to 29 years [34,[42][43][44]. However, these studies observed a minimal effect on breathing pattern after early infancy, which is in line with our study in older infants and children demonstrating no difference in VT and RR between N 2 -and SF 6 -MBW (Table 2).…”
Section: Discussionsupporting
confidence: 90%
“…Taking all into account, it seems unlikely that the different software versions used in our study with their inherent algorithms to process signals to MBW parameters are a major determinant contributing to differences between N 2 -and SF 6 -LCI observed. Some studies detected a decrease in VT during inhalation of 100% O 2 in infants, preschool children, and even young adults of up to 29 years [34,[42][43][44]. However, these studies observed a minimal effect on breathing pattern after early infancy, which is in line with our study in older infants and children demonstrating no difference in VT and RR between N 2 -and SF 6 -MBW (Table 2).…”
Section: Discussionsupporting
confidence: 90%
“…The lower VT during nitrogen washout seems to be a consequence of hyperoxic conditions during washout phase ("peripheral chemodenervation") [8,9]. Although the VT recovers or even exceeds the normoxic values after approximately 60 s, in the end effect, average VT is lower compared to normoxaemia.…”
mentioning
confidence: 98%
“…
Breathing 100% oxygen has been reported to decrease tidal volume (VT) in infants [1] and recent evidence published in the European Respiratory Journal suggest that transient less pronounced effects are also seen in preschool children [2]. It is unclear whether there is an age dependency beyond infancy in the response to 100% oxygen or whether it is limited to young children.
…”
mentioning
confidence: 99%